Pengaruh Knowledge Sharing Terhadap Kinerja Karyawan di PT. Telekomunikasi Indonesia Witel Bandung - Rosyida Nur Laili; M. Yahya Arwiyah (SOSIOHUMANITAS, 2019)
Employee performance was the result of work that have strong ties with the strategic objectives of the organization, consumer satisfaction and contribute to the economy. knowledge sharing is one that affects employee performance. Variables considered knowledge sharing that can affect employee performance is knowledge donating and knowledge collecting. This study aims to determine how knowledge sharing in PT Telecommunication Indonesia Witel Bandung, and how employee performance in PT Telecommunication Indonesia Witel Bandung, how the effect of knowledge sharing which consists of knowledge donating and knowledge collecting partially on employee performance, and how the influence of knowledge sharing which consists of knowledge donating and knowledge collecting simultaneously on employee performance in PT Telecommunication Indonesia Witel Bandung. Data analysis techniques in this study using path analysis with SPSS for Windows version 22. In this study took a sample of 63 employees of PT Telecommunication Indonesia Witel Bandung. Data were collected using a questionnaire containing 30 items related statement of knowledge donating, knowledge collecting and employee performance. Descriptive analysis showed that the percentage of the value of knowledge sharing as a whole amounted to 77.7% categorized as good, where the value of a variable percentage of 81.11% knowledge donating and knowledge collecting a variable percentage of 74.34%. Employee performance variables are categorized either by the amount of the percentage value 80.14%. The results of path analysis showed that partial knowledge of the donating significant influence amounted to 66.0%, while the variable knowledge collecting significant influence amounted to 28.7% of the variable employee performance. Simultaneously knowledge sharing with the two previously mentioned variables that significantly influence employee performance in PT Telecommunication Indonesia Witel Bandung at 78.9%